Community Perceptions of Disaster Recovery Program after the February 2019 Earthquake in Sangir Balai Janggo District, Solok Selatan Regency, West Sumatera Indonesia - Novita, Tila; Umar, Iswandi (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This research was aimed to analize community perception of disaster recovery after the February 2019 earthquake in Solok Selatan . It used a qualitative method and interactive analysis. The research location was Sangir Balai Jonggo in Solok Selatan Regency. Observation, interview, document study and FGD were conducted to collect desired data. Two types of data were obtained. Primary data were collected from the informants selected through purposive sampling including the local community and the government in the affected area, while secondary data were obtained from related local literatures. The informants were Sekcam (District Head) and the community affected by the disaster in Sangir Balai Janggo, Solok Selatan. Physical recovery was done in the 3 most damaged nagaris (village). One of them is Nagari.Sungai Kunyit. There were 67 severely damaged houses, 91 were moderately damaged, and 192 were slightly damaged. Futhermore, the earthquake also affected the facilities in 4 nagaris in Sangir Balai Jonggo; 6 medical centres, 28 schools, and 18 mosques. The result showed that most community were satisfied with the recovery program and they gave positive feedback especially on the aid given to them. The recovery included donation for the victims like basic foods, clean water, instant foods, baby supplies, etc, therapy treatment by doctors and volunteers to help with their mental state and to build their confidence after the earthquake. Key Words: Perception, Disaster, Recovery.